3. Efficacy of Jatropha (Jatropha curcas L) Cream sap Leucocytes in Inflammation Phase of Wound Healing - Mita Nasuha Risky; Triva Murtina Lubis; M. Nur Salim; Teuku Zahrial Helmi; Abdul Harris; Hennivanda Hennivanda; Dian Masyitha; Cut Dahlia Iskandar; Fitriani Fitriani; Abdul Hamzah; T. Fadrial Karmil (Universitas Syiah Kuala, 2020)
This study aims to determine the efficacy of giving jatropha cream (Jatropha curcas L.) on the number of leukocytes in the inflammatory phase of wound healing in the mice’s skin. The method used is literature study research with qualitative techniques. The data used in this study comes from the result of studies that have been conducted and published in national or international online journals. References used are all research articles with data selection. The results of data analysis showed that the administration of jatropha cream (Jatropha curcas L.) was effective in limiting or inhibiting the accumulation of leukocytes in the area of inflammation and could stimulate the formation of new blood vessels (angiogenesis) in the inflammatory phase of wound healing of the mice’s skin. Based on these data it can be concluded that the efficacy of jatropha cream (Jatropha curcas L.) affects the number of leukocytes in the inflammatory phase of wound healing of mice's skin.